Laboratory sampling: does the process affect the outcome? - Becan-McBride K (Journal of Intravenous Nursing)
With the rapidly changing healthcare environment, one of the many increasing tasks for the intravenous team is blood sampling. Laboratory test results are based on the quality of the patient's blood specimen. The preanalytic phase of laboratory testing accounts for 46% of laboratory testing errors, so it needs to be managed effectively to eliminate costly, inefficient, and sometimes life-threatening outcomes to patients. The use of quality blood collection procedures and an awareness of preanalytic errors are presented to lead to quality patient outcomes.